Palynological study of subfamily Caesalpiniodeae species (Fabaceae) in Baghdad (Iraq) - Kurdi, Warud H. Hammadi Al; Al-Dobaissi, Israa A. M. (Phytotaxa, 2025)
Pollen morphology characterization is an important field in taxonomy. This study aims to identify and characterize the pollen morphology for fourteen species from subfamily Caesalpiniodeae (Fabaceae). The results showed the similarity of all species pollen in terms of being monad and tri,zono-colporate type, and each Ceratonia siliqua and Senna occidentalis distinguished by having tetra,zono-colporate pollen as well, and the results revealed the prevalence of reticulate configuration in most studies species, while Ceratonia siliqua characterized by striates configuration, Cassia fistula distinguished by verrrucate-gemmate wall, and Senna species by verrrucate- perforate, as for the shape, showed a discrepancy in the general shape from the oblate shape through the spherical to the semi-prolate, and variability in both polar and Equatorial views as well as pollen size that ranging from small and medium to large size, in addition to the observation of synapertures feature in Erythrostemon gillissi.